Energy-Aware Virtual Machine Consolidation for Cloud Data Centers - Alboaneen, Dabiah Ahmed; Pranggono, Bernardi; Tianfield, Huaglory (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
One of the issues in virtual machine consolidation (VMC) in cloud data centers is categorizing different workloads to classify the state of physical servers. In this paper, we propose a new scheme of host's load categorization in energy-performance VMC framework to reduce energy consumption while meeting the quality of service (QoS) requirement. Specifically the under loaded hosts are classified into three further states, i.e., Under loaded, normal and critical by applying the under load detection algorithm. We also design overload detection and virtual machine (VM) selection policies. The simulation results show that the proposed policies outperform the existing policies in Cloud Sim in terms of both energy and service level agreements violation (SLAV) reduction.